The Bourne Supremacy - Ludlum, Robert (New York Bantam Books, 1987)
Super-diplomat Raymond Havilland sets up the kidnapping of Jason Bourne's wife, in order to draw Bourne out of retirement and into a Taiwanese plot to seize Hong Kong and incite China against the West.
Keywords: Terrorists -- Carlos, the Jackal -- Assassination